2022
DOI: 10.3389/fpls.2022.777308
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Analysis Uncovers Hub Long Non-coding RNAs Regulating Potassium Use Efficiency in Nicotiana tabacum

Abstract: Potassium (K) is the essential element for plant growth. It is one of the critical factors that determine crop yield, quality, and especially leaf development in tobacco. However, the molecular mechanism of potassium use efficiency (KUE), especially non-coding RNA, is still unknown. In this study, tobacco seedlings were employed, and their hydro-cultivation with K treatments of low and sufficient concentrations was engaged. Physiological analysis showed that low potassium treatment could promote malondialdehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…TCONS_00009717 is a miRNA found in soybean that may be induced by salt stress, its potential target is cytochrome P450 ( Chen et al, 2019 ). Summarily, LncRNAs were also discovered and found to be involved in response to several abiotic stresses in plant species such as Arabidopsis thaliana , Zea may , and Nicotiana tabacum ( Liu et al, 2012 ; Lv et al, 2013 , 2019 ; Yu et al, 2019 ; Zhang et al, 2019 , 2021 ; Chen et al, 2022 ). However, as a remarkable salt tolerant crop, the LncRNAs of quinoa responding to salt stress have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TCONS_00009717 is a miRNA found in soybean that may be induced by salt stress, its potential target is cytochrome P450 ( Chen et al, 2019 ). Summarily, LncRNAs were also discovered and found to be involved in response to several abiotic stresses in plant species such as Arabidopsis thaliana , Zea may , and Nicotiana tabacum ( Liu et al, 2012 ; Lv et al, 2013 , 2019 ; Yu et al, 2019 ; Zhang et al, 2019 , 2021 ; Chen et al, 2022 ). However, as a remarkable salt tolerant crop, the LncRNAs of quinoa responding to salt stress have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been discovered to be involved in a variety of biological regulatory processes, and their expression patterns are more tissue-specific than mRNA ( Ponting et al, 2009 ; Rinn and Chang, 2012 ). According to their relative positions to nearby protein-coding genes in the genome, LncRNAs are generally classified into five types: sense, antisense, bidirectional, intergenic, and intronic ( Liu et al, 2012 ; Lv et al, 2019 ; Chen et al, 2022 ). Previous studies have indicated that plant LncRNAs play functional roles in signal pathway transmission and molecular regulation under abiotic stresses such as salt stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenomics studies are mainly about non-coding RNAs and alternative mRNA splicing (AS). Long Non-coding RNAs sense environmental K concentrations and play regulatory roles in the K response network ( Chen et al., 2022 ). AS modulation is independent of transcription regulation and plays a unique regulatory role in response to low potassium ( He et al., 2021 ).…”
Section: Omics Data-driven Kue Breedingmentioning
confidence: 99%
“…However, LncRNA, especially transposon-derived LncRNAs (TE-LncRNA), is still not fully understood or even illustrated. After the introduction of new generation sequencing technology, the high-through transcriptome analysis has facilitated the discovery of LncRNA greatly ( Lv et al, 2019 ; Chen et al, 2022 ; Liang et al, 2022 ). Recently, LnRNAs were predicted and verified in the transcriptome of F. vesca fruit in altering stages ( Kang and Liu, 2015 ).…”
Section: Introductionmentioning
confidence: 99%